Effect of systemic therapies or best supportive care after disease progression to both nivolumab and cabozantinib in metastatic renal cell carcinoma: The Meet‐Uro 19BEYOND study. (20th March 2022) - Roviello, Giandomenico; Gambale, Elisabetta; Giorgione, Roberta; Santini, Daniele; Stellato, Marco; Fornarini, Giuseppe; Rebuzzi, Sara Elena; Basso, Umberto; Bimbatti, Davide; Doni, Laura; Nesi, Gabriella; Bersanelli, Melissa; et al.
Abstract: Background: Nivolumab and cabozantinib are currently approved agents in metastatic renal cell carcinoma (mRCC) but there are no data available for patients progressing to both treatments. The aim of this study was to compare active therapeutic options and best supportive care (BSC) after progression to nivolumab and cabozantinib in mRCC. Methods: In this retrospective study, we selected 50 patients from eight Italian centers. The primary endpoint of the study was the overall survival (OS) of patients on active treatment versus BSC. Secondary endpoints were the progression‐free survival (PFS) and objective response rate (ORR). The efficacy of active therapy was also investigated. Results: After progression to both nivolumab and cabozantinib, 57.1% of patients were given active treatment (mainly everolimus and sorafenib) while 42.9% received BSC. The median OS was 13 months (95% CI: 4‐NR) in actively treated patients and 3 months (95% CI: 2–4) in BSC patients ( p = 0.001). Patients treated with sorafenib had better disease control than those treated with everolimus (stable disease: 71.4% vs. 16.7%, progression disease: 14.3% vs. 58.3%; p = 0.03), with no significant differences in PFS (5 and 3 months, 95% CI: 1–6 vs. 2–5; p = 0.6) and OS (12 and 4 months, 95% CI: 3‐NR vs. 2‐NR; p = 0.2). Conclusion: After treatment with both nivolumab and cabozantinib, the choice of a safe active systemic therapy offered better outcomes than BSC. Abstract : In this paper, we report the results of our retrospective analysis of mRCC treated before the approval of 1 L‐ anti‐PD1 based combination, with the aim to compare the treatment choices after progression to nivolumab and cabozantinib including patients followed in BSC or active therapy.